Peningkatan Hasil Belajar Materi Dialog Antarumat Beragama Melalui Video YouTube di SMAN 1 Kembayan - Romanus Andus; Hartutik Hartutik (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This study is based on the issues faced by Catholic students in class XII MIPA 1 at SMAN 1 Kembayan, particularly their lack of motivation to learn and difficulty in collaborating with peers of different religious backgrounds. Students tend to prefer working with those who share the same religion, indicating a limited openness toward diversity. The conventional lecture-based teaching approach used by teachers has proven to be less effective in fostering values of tolerance and pluralism. Therefore, this study aims to investigate the improvement in students' learning outcomes within the dimension of global diversity, focusing on both the affective (behavioral) and cognitive (academic performance) aspects through the implementation of the Problem Based Learning (PBL) model in the topic of Interreligious Dialogue and Cooperation. This is a Classroom Action Research (CAR) conducted in two cycles involving 14 students. Each cycle consists of four stages: planning, action, observation, and reflection. The main focus is on the global diversity dimension of the Pancasila Student Profile to strengthen affective values. Data analysis was conducted using descriptive quantitative methods in the form of percentages. The results show a significant improvement in the affective aspect, with the average score increasing from 63.2 to 86.2 (an increase of 23%), and in the cognitive aspect, from an average of 68.21 to 84.57 (an increase of 16.36 points). In conclusion, the implementation of the Problem Based Learning model with a focus on a specific Pancasila Student Profile dimension effectively enhances students' learning outcomes and their attitudes toward diversity.